Sustainable Supercapacitor Electrode: The Role of Performance-Activated Carbon from Nypa Fruticans Shells - Muhammad Iqbal Al Fuady; Ilmi Utari Simatupang; Putri Khoyrul Afifah (Program studi Teknik Kimia UNS, 2024)
Abstract. Supercapacitors are energy storage devices widely used in electronics, representing a significant breakthrough in energy storage technology. Known as electric double-layer capacitors (EDLC), supercapacitors are electrochemical energy storage systems with higher power density than batteries. The material used to produce supercapacitor electrodes is waste from Nypa shells. The Nypa shells contain 36.5% cellulose, 21.8% hemicellulose, and 27.3% lignin. The production process uses the pyrolysis method to produce activated carbon, which is then used as supercapacitor electrode material. The SEM (Scanning Electron Microscope) test shows that all samples have different pore cavity structures in activated carbon. The EDX (Energy Dispersive X-ray) test shows that all activated carbon samples contain C, O, Mg, Si, and Ca elements. Based on FTIR (Fourier transform Infrared Spectroscopy) analysis showed that all samples had the same wave pattern and the presence of functional groups in the form of O-H, C=C, C-H, and C ≡ C was detected. The BET test (Brunauer – Emmett – Teller) shows that activated carbon with C-NPS-Ox has a specific surface area, micropore surface area, total pore volume, and average pore diameter values of 989.3 m2/g, 537.1 m2/g, 56.5 cm3/g, and 11.4 nm. The CV (Cyclic Voltammetry) test shows that the C-NPS-Ox sample with a scan rate of 10 mV/s has the highest specific capacitance value, 142.44 F/g. Keywords:Nypa Palm Shell, Activated Carbon, Electrode, Supercapacitor.